2011
DOI: 10.1029/2010gl045999
|View full text |Cite
|
Sign up to set email alerts
|

Optical and microphysical properties of fresh biomass burning aerosol retrieved by Raman lidar, and star-and sun-photometry

Abstract: [1] A fresh biomass-burning pollution plume was monitored and characterized in terms of optical and microphysical properties for the first time with a combination of Raman lidar and star-and sun-photometers. Such an instrument combination is highly useful for 24-h monitoring of pollution events. The observations were made at Granada (37.16°N, 3.6°W), Spain. The fresh smoke particles show a rather pronounced accumulation mode and features markedly different from those reported for aged particles. We find lidar … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

24
129
2

Year Published

2012
2012
2017
2017

Publication Types

Select...
8

Relationship

6
2

Authors

Journals

citations
Cited by 148 publications
(155 citation statements)
references
References 15 publications
24
129
2
Order By: Relevance
“…The "color ratio of lidar ratios" (CR LR = LR532 / LR355) reached values around 2 for GR and LE, which hints towards the aging process. It has been demonstrated that CR LR < 1 is usual for fresh smoke particles, while CR LR > 1 corresponds to aged smoke (Müller et al, , 2007aAlados-Arboledas et al, 2011;. The latter comparison among the results obtained and other values found in the literature about biomass burning events detected in Europe is summarized in Table 3.…”
Section: Optical Propertiessupporting
confidence: 58%
See 2 more Smart Citations
“…The "color ratio of lidar ratios" (CR LR = LR532 / LR355) reached values around 2 for GR and LE, which hints towards the aging process. It has been demonstrated that CR LR < 1 is usual for fresh smoke particles, while CR LR > 1 corresponds to aged smoke (Müller et al, , 2007aAlados-Arboledas et al, 2011;. The latter comparison among the results obtained and other values found in the literature about biomass burning events detected in Europe is summarized in Table 3.…”
Section: Optical Propertiessupporting
confidence: 58%
“…Very low imaginary parts of the refractive index (IRI) with values form 0.0012 to 0.003 compared to 0.0094 ± 0.003, given by Dubovik et al (2002), and single scattering albedos close to 1 indicate a weak absorption by the particles, and therefore a low black carbon fraction, in disagreement with some previous works about biomass burning particles Alados-Arboledas et al, 2011) but in agreement with others (Eck et al, 2009;Samaras et al, 2015). The spectral dependence of the SSA between 355 and 532 nm shows what could be considered an anomalous behavior compared to some columnar retrievals (Reid et al, 2005a, b;Dubovik et al, 2002), where biomass burning aerosol SSA typically decreases with increasing measurement wavelength.…”
Section: Microphysical Propertiescontrasting
confidence: 51%
See 1 more Smart Citation
“…An SSA range of 0.5-1.0 was used to represent the wide range in SSA for biomass burning aerosols found in the literature (e.g., Bergstrom et al, 2003;Johnson et al, 2008;Lewis et al, 2008;Eck et al, 2009;Mack et al, 2010;Alados-Arboledas et al, 2011;Tesche et al, 2011). The differences in SSA among biomass burning aerosols is likely explained by observed differences in combustion conditions generated by different fuel types, humidities, etc.…”
Section: Ssa Retrievalmentioning
confidence: 99%
“…Atmospheric aerosol optical properties have been widely investigated in the city of Granada at surface level (e.g., Lyamani et al, 2008;Lyamani et al, 2010;Titos et al, 2012;Segura et al, 2014), in the vertical column with height resolution (e.g., GuerreroRascado et al, 2008;Alados-Arboledas et al, 2011;Bravo-Aranda et al, 2015 and references therein) and column-integrated (e.g., Lyamani et al, 2005;Valenzuela et al, 2012). The meteorological conditions together with the topography of the city sited in a valley surrounded by mountains of high elevation (about 3500 m a.s.l.)…”
Section: Introductionmentioning
confidence: 99%